Eriosema elegans (Leguminosae, Papilionoideae): A new species from the Highlands of Goiás State, Brazil - Fortuna-Perez, Ana Paula; Silva, Marcos José Da; Cândido, Elisa Silva; de Vargas, Wanderleia; Monteiro, Thiago Cobra E; Vatanparast, Mohammad (Phytotaxa, 2017)
During a taxonomic study of Eriosema in Brazil, a new species was discovered from the Chapada dos Veadeiros National Park, Goiás State. Eriosema elegans is herein described and illustrated and its morphological affinities with related species discussed. The geographical distribution, conservation status, and information about flowering and fruiting are provided. Also, a study of secretory structures of leaflets of the new species and the morphologically related species E. glabrum was carried out.